2005
DOI: 10.1128/jcm.43.2.843-849.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Microbial Diversity in Advanced Caries

Abstract: Real-time PCR analysis of the total bacterial load in advanced carious lesions has shown that the total load exceeds the number of cultivable bacteria. This suggests that an unresolved complexity exists in bacteria associated with advanced caries. In this report, the profile of the microflora of carious dentine was explored by using DNA extracted from 10 lesions selected on the basis of comparable total microbial load and on the relative abundance of Prevotella spp. Using universal primers for the 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
2
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(189 citation statements)
references
References 36 publications
14
167
2
6
Order By: Relevance
“…In this study, 9 samples showed higher level of Olsenella. Another study conducted by Chhour et al in 2005 showed the presence of Olsenella in two samples. [20] Parascardovia and Scardovia belong to the family Bifidobacteriaceae, which was found to be 17.3% in this study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, 9 samples showed higher level of Olsenella. Another study conducted by Chhour et al in 2005 showed the presence of Olsenella in two samples. [20] Parascardovia and Scardovia belong to the family Bifidobacteriaceae, which was found to be 17.3% in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Another study conducted by Chhour et al in 2005 showed the presence of Olsenella in two samples. [20] Parascardovia and Scardovia belong to the family Bifidobacteriaceae, which was found to be 17.3% in this study. Mantzourani et al demonstrated that Scardovia, and Parascardovia were associated with cavitated caries lesions, together with S. mutans, Lactobacilli, and yeasts, indicating that the acidic environment of the lesions provided a suitable habitat for the proliferation of these aciduric microorganisms.…”
Section: Discussionmentioning
confidence: 91%
“…et al, 2002;Hold et al, 2002;Eckburg et al, 2005;Zhongtang et al, 2005;Frank et al, 2007). Furthermore, culture-independent analysis identified Lachnospiraceae-affiliated bacteria to be present in the biofilms adherent to plant biomass recovered from ruminants (Zhongtang et al, 2005) and the oral cavity in humans (Chhour et al, 2005).…”
Section: Biofilm (A595)mentioning
confidence: 99%
“…[1][2][3][4] Lactobacilli produce lactic acid, reducing the environmental pH, 5) and therefore, they can produce acidic environmental niches, such as the oral cavity. 6) Some studies showed that oral administration of Lactobacilli increased the levels of Lactobacilli in human feces and also decreased the numbers of fecal Escherichia coli and Anaerobic cocci. 7,8) These studies indicated that lower pH environment brought about by lactic acid could decrease the other bacteria such as Enterobacteriaceae.…”
mentioning
confidence: 99%